Infrequent alterations of the RARα gene in acute myelogenous leukemias, retinoic acid-resistant acute promyelocytic leukemias, myelodysplastic syndromes, and cell lines - Morosetti, Roberta; Grignani, Francesco; Liberatore, Concetta; Pelicci, Pier Giuseppe; Schiller, Gary J.; Kizaki, Masahiro; Bartram, Claus R.; Miller, Carl W.; Koeffler, H. Phillip (Blood, 1996)
Retinoids are important regulators of cell growth and differentiation in vitro and in vivo and they exert their biologic activities by binding to nuclear retinoic acid receptors (RARs; α, p, and γ) and retinoid X receptors (RXRs; α, β, and γ). All-trans retinoic acid (RA) induces complete remission in patients with acute promyelocytic leukemia (APL) presumably by binding directly to RARα of APL cells. Leukemic blasts from APL patients initially responsive to RA can become resistant to the agent. HL-60 myeloblasts cultured with RA have developed mutations of the ligand-binding region of RARα and have become resistant to RA. Furthermore, insertion of an RARα with an alteration in the ligand-binding region into normal murine bone marrow cells can result in growth factor-dependent immortalization of the early hematopoietic cells. To determine if alterations of the ligand binding domain of RARα might be involved in several malignant hematologic disorders, the mutational status of this region (exons 7, 8, and 9) was examined in 118 samples that included a variety of cell lines and fresh cells from patients with myelodysplastic syndromes (MDS) and acute myeloid leukemias (AMD, including 20 APL patients, 5 of whom were resistant to RA and 1 who was refractory to RA at diagnosis, using polymerase chain reaction-single-strand conformational polymorphism (PCR-SSCP) analysis and DNA sequencing. In addition, 7 of the 20 APLs were studied for alterations of the other coding exons of the gene (exons 2 through 6). No mutations of RARα were detected. Although the sensitivity of PCR-SSCP analysis is less than 100%, these findings suggest that alterations of RARα gene are rare and therefore other mechanisms must be involved in the onset of resistance to retinoids and in the lack of differentiation in disorders of the myeloid lineage.